(untitled) (Research, Society and Development, 2022)
Mammary gland neoplasms have a multifactorial origin and are classified as the main type of neoformation that affects cats. The diagnosis is obtained from histopathological analysis, where it is possible to determine the type and histological grade of the breast tumor. More recently, tissue biomarkers have allowed more accurate analyzes of the degree of malignancy of tumors, with an attempt to use serum markers to diagnose micronodules and metastases early. Thus, this study aimed to characterize the clinical profile and evaluate the serum levels of carcinoembryonic antigen (CEA) and carcinogen antigen 15.3 (CA15.3), quantified by ELISA. In addition, the objective was to define the histopathological diagnosis and identify the immunohistochemical profile of cyclooxygenase-2 (COX-2) in breast neoplasms. The study was carried out in 49 cats, 38.78% were not neutered and 59.18% had already been submitted to contraceptive hormones. Malignant neoplasms accounted for 76.92%, with the cribriform, tubulopapillary and tubular types being the most frequent. The mean serum levels of CA15.3 and CEA were 2.4108 ± 0.4748 U/mL and 0.0024 µg/L, respectively. The mammary tumor in cats is highly malignant, and more than one histological type can coexist in cats with multiple nodules. The immunoexpression of COX-2 and showed no significant association with the appearance of breast tumors. The use of tumor markers CEA and CA15.3 was not efficient in cats with mammary lesions.